636 LOOKING AT THE BIGGER PICTURE: FROM ACUTE MYOCARDITIS TO THE DIAGNOSIS OF A MULTISYSTEMIC DISEASE. (15th December 2022) - Scuppa, Maria Francesca; Manno, Stefania; Masetti, Marco; Prestinenzi, Paola; Russo, Antonio; Sabatino, Mario; Spitaleri, Giosafat
Abstract: A 49-year-old man without cardiovascular risk factors, recently diagnosed of asthma and rino-sinusal polyposis, entered the Emergency Department for chest pain, shortness of breath and non-productive cough. The patient was in stable conditions. Laboratory exams showed eosinophilic leucocytosis (WBC 33.000/sqmm, 60% eosinophils) and a mild elevation of C-reactive protein (CRP 2, 2 mg/dL). ECG showed a sinus rhythm with flat T-waves in the antero-lateral leads. Troponin values were high but not suggestive of acute myocardial damage (9900 - 9700 ng/L). Echocardiography showed normal biventricular volumes with moderately depressed left ventricular ejection fraction (40%), hypokinesia of the antero-lateral wall in the mid-apical segments and mild pericardial effusion. During the hospital stay he developed progressive respiratory failure, and he was transferred to a tertiary center to perform an endomyocardial biopsy (EMB) in the suspicion of acute myocarditis. EMB showed multifocal interstitial and sub-endocardial inflammatory infiltrates (predominantly eosinophils) with foci of myocellular damage, small vessels wall inflammation with hypertrophy of the muscular tunica. The overall picture was consistent with diffuse moderate eosinophilic myocarditis with small vessels vasculitis. The right heart cath performed in the same procedure and during diuretic therapy showed a normal hemodynamic profile (RAP 5 mmHg, PCWP 13 mmHg, CI 3, 7 L/min/sqm). The patient was treated with high dose steroids, first intravenously (methylprednisolone 125 mg/day for three days), then orally (prednisone 80 mg/day) in slow decalage until a maintenance dose of 12.5 mg daily. The recent-onset of asthma with hyper-eosinophilia and rhino-sinus-bronchial syndrome in the light of the present cardiac condition was consistent with eosinophilic granulomatosis with polyangiitis (EGPA). Chest CT showed two areas of ground glass at the left superior and right superior lobes. Other potential haematological and infective causes of hyper eosinophilia and viral causes of myocarditis were ruled out. After the treatment, his clinical conditions improved, ECG was completely normalized, left ventricular systolic function improved (LVEF 50%) and eosinophil count was significantly reduced (Eosinophils 830/sqmm, 8, 9%), whereas CT showed resolution of the lung infiltrates. One month after discharge, the patient was still asymptomatic. Cardiac MRI showed normal biventricular ejection fraction (LVEF 55%) with circumferential subendocardial fibrosis involving only the left ventricle. EMB showed a complete resolution of the inflammatory infiltrates and of the vasculitic aspects. Eosinophil count was elevated (5660/sqmm, 36%). Therefore, steroidal dose was raised to 50 mg/day. After rheumatologic evaluation, a steroidal sparing strategy with cyclophosphamide and anti-IL5 antibody Mepolizumab was adopted, with good laboratory response. Three months later, cardiac MRI showed no signs of active disease. No further EMB was scheduled. Through the presentation of this unusual cause of acute myocarditis, we want to underscore the importance of an early referral to a tertiary level center of patients with suspected myocarditis and reduced systolic function and the usefulness of histology to guide medical therapy in specific forms of myocarditis that can lead to a potential complete recovery.